2022
DOI: 10.1021/acssuschemeng.1c08558
|View full text |Cite
|
Sign up to set email alerts
|

Ultralong-Chain Ionic Liquid Surfactants Derived from Natural Erucic Acid

Abstract: Ionic liquid surfactants (ILSs) have shown increasing promise for substituting the traditional amphiphiles because of their flexible tunability and advantageous physicochemical properties. However, the improvement of common ILSs in terms of self-assembly ability and thickening ability remains a significant challenge. Herein, two novel ultralong-chain ILSs (ULILSs), ErBCho (choline cis-4-erucylamidobenzoate) and ErBBTA (benzyltrimethylammonium cis-4-erucylamidobenzoate), were designed and synthesized from natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The presence of a WLM network is indicated when the transition of the increasing trend shifts from linear to exponential. The breakpoint is often termed the critical overlapping concentration (C*), which was calculated to be 4.43 wt % …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of a WLM network is indicated when the transition of the increasing trend shifts from linear to exponential. The breakpoint is often termed the critical overlapping concentration (C*), which was calculated to be 4.43 wt % …”
Section: Resultsmentioning
confidence: 99%
“…The lower melting point of BD-OA could be attributed to the significant volumetric asymmetry between the fatty acid anions and quaternary ammonium counterions, which prevent the formation of strong electrostatic interactions and tight crystal packing. 41 Additionally, TGA experiments demonstrated the onset of decomposition of BD-OA at 290.5 °C (Figure S3), indicating its remarkable thermal stability. The results from DSC and TGA results both revealed that BD-OA falls within the category of ILSs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good proppant‐carrying capacity of fracturing fluids is required to possess sufficient strength to deliver proppant evenly into the fractures (Hari et al, 2021). If the proppant‐suspending capacity of fracturing fluid is poor, proppants will drop rapidly and cannot be transported into the deep fractures of reservoirs, so it is significant to carry out the proppant‐suspending test (Zhang et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The temperature resistance of the formed blending surfactant systems can reach 160 °C, but no other fracturing fluid performance test data was provided. Zhang et al 268 found that using benzyltrimethylammonium cation instead of choline cation can further reduce the cmc of the erucic-based VES fluids and improve the temperature resistance. Due to the insertion of phenyl into the hydrophobic region formed by the erucic acid tails, the arrangement among surfactants is more compact.…”
Section: Counterion Salt Effectmentioning
confidence: 99%